PENGARUH MODEL PEMBELAJARAN PAIR CHECK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD INPRES 6/75 MANURUNGE KECAMATAN TANETE RIATTANG KABUPATEN BONE - Jafar, Muh Idris; Muin, Awaluddin; Hikmah, Nur (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is an experimental study aimed at determining the effect of the Pair Check learning model on the mathematics learning outcomes of fourth-grade students at SD Inpres 6/75 Manurunge. The research design used is Pre-Experimental with a One Group Pretest-Posttest Design. The population in this study consisted of fourth-grade students at SD Inpres 6/75 Manurunge, with a sample of 20 students selected using a saturated sampling technique. The data collection technique used was a test to determine the mathematics learning outcomes of students before and after the implementation of the Pair Check learning model. The data analysis used descriptive and inferential statistical analysis. Based on the results of descriptive statistical analysis, the average pretest score was 56,50, while the average posttest score was 73. The obtained data were then analyzed using a Paired sample t-test with a significance level of 5%. The data analysis resulted in 9,079 > 2,093. Therefore, t-count > t-table, meaning H0 is rejected, indicating a significant effect of the Pair Check learning model on the mathematics learning outcomes of fourth-grade students at SD Inpres 6/75 Manurunge, Tanete Riattang District, Bone Regency.